2009 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2009
DOI: 10.1109/iembs.2009.5332746
|View full text |Cite
|
Sign up to set email alerts
|

A fuzzy logic model for hand posture control using human cortical activity recorded by micro-ECog electrodes

Abstract: This paper presents a fuzzy logic model to decode the hand posture from electro-cortico graphic (ECoG) activity of the motor cortical areas. One subject was implanted with a micro-ECoG electrode array on the surface of the motor cortex. Neural signals were recorded from 14 electrodes on this array while Subject participated in three reach and grasp sessions. In each session, Subject reached and grasped a wooden toy hammer for five times. Optimal channels/electrodes which were active during the task were select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Micro-ECoG is becoming increasingly popular for its ability to provide higher temporal and spatial resolution than typical ECoG [6,17,32,33], often comparable to intracortical microelectrodes [33,34]. A major advantage is the smaller size of the electrode site, which allows for more precise and accurate readings and less invasive implantation than its ECoG predecessor [17,33,34].…”
Section: Evolution Of Ecog Into μEcogmentioning
confidence: 99%
“…Micro-ECoG is becoming increasingly popular for its ability to provide higher temporal and spatial resolution than typical ECoG [6,17,32,33], often comparable to intracortical microelectrodes [33,34]. A major advantage is the smaller size of the electrode site, which allows for more precise and accurate readings and less invasive implantation than its ECoG predecessor [17,33,34].…”
Section: Evolution Of Ecog Into μEcogmentioning
confidence: 99%
“…This work guided development of subsequent human study protocols and IDE applications. Finally, the EMU study generated critical pilot data and initial funding from multiple agencies that made it possible for us to form and grow our clinical BCI research team with a demonstrated track record. The EMU research conducted in patients undergoing clinical brain mapping in itself has important scientific, engineering, and clinical value as exemplified by the ever‐increasing number of research groups and publications based on this study setting …”
Section: Foundational Studiesmentioning
confidence: 99%
“…The EMU research conducted in patients undergoing clinical brain mapping in itself has important scientific, engineering, and clinical value as exemplified by the ever-increasing number of research groups and publications based on this study setting. [23][24][25][26][27][28][29][30][31][34][35][36][37][38][39][40][41][42][43]…”
Section: Ecog Studies In the Emumentioning
confidence: 99%
“…A micro-ECoG grid with 14 recording electrodes was implanted over the motor cortical area, and it was found that the high frequency band of neural signals recorded from this micro-ECoG grid showed significant modulation by hand movement, including individual finger movement 45 and grasping/pinching movement of the hand 46. Modulation of micro-ECoG signals by hand movement offers a neural substrate that is critical to the success of a BCI system aiming to restoring volitional control of finger movement.…”
Section: Neural Interface Technology For Neural Recordingmentioning
confidence: 99%